2010
DOI: 10.1099/mic.0.037812-0
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical conservation of a set of three cellulose-targeting genes in Mycobacterium tuberculosis complex organisms

Abstract: The genome of the tuberculosis agent Mycobacterium tuberculosis encodes a putative cellulosebinding protein (CBD2), one candidate cellulase (Cel12), and one fully active cellulase (Cel6). This observation is puzzling, because cellulose is a major component of plant cell walls, whereas M. tuberculosis is a human pathogen without known contact with plants. In order to investigate the biological role of such cellulose-targeting genes in M. tuberculosis we report here the search for and transcription analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…These data agree with the previous demonstration that M. tuberculosis organisms, but not M. avium organisms, were ejected from the amoeba Dictyostelium trophozoite by using an actin-based ejectosome [12]. MTC organisms may rely on their unique cellulase equipment, which are sugar cleaving enzymes capable of hydrolysing cellulose, a major component of the amoebal cyst cell wall [31], [32], to bypass amoebal cysts; the MTC organisms which still resided into the amoebal cyst, did resist glutaraldehyde, a biocide used to decontaminate medical devices, after entrapment in the amoebal cyst.…”
Section: Discussionsupporting
confidence: 92%
“…These data agree with the previous demonstration that M. tuberculosis organisms, but not M. avium organisms, were ejected from the amoeba Dictyostelium trophozoite by using an actin-based ejectosome [12]. MTC organisms may rely on their unique cellulase equipment, which are sugar cleaving enzymes capable of hydrolysing cellulose, a major component of the amoebal cyst cell wall [31], [32], to bypass amoebal cysts; the MTC organisms which still resided into the amoebal cyst, did resist glutaraldehyde, a biocide used to decontaminate medical devices, after entrapment in the amoebal cyst.…”
Section: Discussionsupporting
confidence: 92%
“…The mechanisms and biological significance of this particular location remain to be studied. It has been established that A. polyphaga exocyst is composed of cellulose [43] and the authors have observed that mycobacteria encode one cellulose-binding protein and one or two cellulases which are indeed transcribed [44]. Cellulase encoded by mycobacteria may play a role in their unique exocyst location.…”
Section: Resultsmentioning
confidence: 99%
“…38;68 Additionally, although M. tuberculosis can subsist on a variety of carbon sources and contains cellulases and other enzymes necessary for the breakdown of cellulose, no xylan degradative enzymes or modules have been found in M. tuberculosis , making LipW unlikely to be an acetyl xylan esterase. 69–71 …”
Section: Discussionmentioning
confidence: 99%